2019
DOI: 10.1177/1474515119885858
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health competence predicts anxiety and depressive symptoms after a three-year follow-up among adolescents and adults with congenital heart disease

Abstract: Background: Congenital heart disease places survivors at increased risk for cardiovascular complications as they age and requires long-term medical management. Perceived health competence, or how capable one feels in managing one’s health, is linked to emotional adjustment in various disease populations, but has not been investigated among congenital heart disease survivors. Aim: The purpose of this study was to examine the relationship of perceived health competence at baseline (T1) as a predictor of anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We observed that nearly 32% of participants reported mild, moderate, or severe anxiety symptoms (HADS-A ≥8). This result is similar or lower than the prevalence of anxiety symptoms found in 2 recent North American studies (35% 22 and 42% 23 ). Nevertheless, the average severity of anxiety symptoms we observed (6 ± 4) is similar to what these 2 studies (6 ± 4 22 , 7 ± 4 23 ) reported, as well as an international study (6 ± 4 24 ).…”
Section: Discussionsupporting
confidence: 80%
“…We observed that nearly 32% of participants reported mild, moderate, or severe anxiety symptoms (HADS-A ≥8). This result is similar or lower than the prevalence of anxiety symptoms found in 2 recent North American studies (35% 22 and 42% 23 ). Nevertheless, the average severity of anxiety symptoms we observed (6 ± 4) is similar to what these 2 studies (6 ± 4 22 , 7 ± 4 23 ) reported, as well as an international study (6 ± 4 24 ).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, individuals who feel more competent in managing their health may be less likely to experience future anxiety and depressive symptoms. 11 These results are in keeping with the findings of a study that was previously published in the Journal, indicating that general self-efficacy predicted anxiety and depression with an explained variance of 5.9% and 13.6%, respectively. 6 In another study, Chang and colleagues scrutinised the relationship between the cyanotic status of CHD and internalising problems, such as anxiety and depression.…”
supporting
confidence: 90%
“…Leslie and co-workers investigated the relationship between perceived health competence and future anxiety and depression in adults with CHD. 11 Perceived health competence refers to how capable one feels in managing one's own health. 11 This construct is closely linked to selfefficacy.…”
mentioning
confidence: 99%
See 2 more Smart Citations